Forgotten Places: Points of confluence in existing urban frameworks - Lenton, Scott (School of Architecture, Planning and Geomatics, 2024)
The notion of Forgotten Place within the urban realm is very intriguing as a narrative from which the revitalization of dilapidated and under-utilized space can be given a new importance. This dissertation addresses the design challenge of revitalizing and reshaping spaces within an existing urban context using specific theoretical principles to help make the legibility of the proposal clear. Currently in our cities, designers face the challenge of generating outdoor environments as communal, inclusive spatial frameworks that propagate new development. Pedestrian connections between important destinations are often disjointed and disturbed, where walking can be a disorienting experience. Identifying these gaps in spatial continuity, then using a set of design principles, these Forgotten Places can be filled with a framework of buildings and interconnected open-space opportunities that will generate new interest and use. These misused spaces have underlying themes which link to the authentic identity of local communities. It is suggested that this meaning is culturally immensely significant, and that remembering these definitions allows for a more integrative and inclusive set of city-making components. Forgotten Places in the existing urban fabric of Port Elizabeth provide an exceptional opportunity to reshape a deteriorating and underused place, so that it attracts people back into powerful places of cultural significance and helps restore communities